Public restrooms, periods, and people experiencing homelessness: An assessment of public toilets in high needs areas of Manhattan, New York. - Andrew R Maroko (Public Library of Science (PLoS), 2021)
Access to safe, clean water and sanitation is globally recognized as essential for public health. Public toilets should be accessible to all members of a society, without social or physical barriers preventing usage. A public toilet facility's design and upkeep should offer privacy and safety, ensure cleanliness, provide required sanitation-related resources, and be gender equitable, including enabling comfortable and safe management of menstruation. Menstrual hygiene management (MHM) refers to the need to ensure that girls, women and all people who menstruate have access to clean menstrual products, privacy to change the materials as often as needed, soap and water for washing the body as required, and access to facilities to dispose of used materials. Challenges around menstruation faced by people experiencing homelessness, which tend to be greater than those facing the general population, include inadequate toilet and bathing facilities, affordability issues around menstrual products, and menstrual stigma. Public toilets are a vital resource for managing menstruation, particularly for vulnerable populations without reliable access to private, safe, and clean spaces and menstrual products. This mixed-methods study sought to: 1) understand the lived experiences of MHM among people experiencing homelessness in New York City with respect to public toilets; 2) describe general and MHM-related characteristics of public toilets in high need areas of Manhattan and analyze their interrelationships; and 3) examine the associations among neighborhood-level demographics and the public toilet characteristics in those areas. Qualitative methods included key informant interviews (n = 15) and in-depth interviews (n = 22) with people with experience living on the street or in shelters, which were analyzed using Malterud's 'systematic text condensation' for thematic cross-case analysis. Quantitative methods included audits and analyses of public toilet facilities (n = 25) using traditional statistics (e.g., Spearman's correlations) and spatial analyses (e.g., proximity buffers). Qualitative findings suggest cleanliness, access to restrooms, and availability of resources are critical issues for the participants or prospective users. Quantitative analyses revealed insufficiently provided, maintained, and resourced public toilets for managing menstruation in high-needs areas. Findings also suggest that toilets with more MHM-related resource availability, such as menstrual products and toilet stall disposal bins, were more difficult to access. Neighborhood-level characteristics showed a potential environmental injustice, as areas characterized by higher socioeconomic status are associated with more access to MHM-specific resources in public restrooms, as well as better overall quality.